Steak for breakfast - O'Conner, Elizabeth, 1913-2000. (Sydney : Arkon, 1973)
Biographical account of life as a station owners wife in the Gulf country of Qld; includes numerous details of Aboriginal domestics and stockmen.
Keywords: Agriculture. Cattle properties. Rural life. Queensland. Gulf of Carpentaria region. Humorous treatments; Country life -- Queensland -- Gulf of Carpentaria district -- Humor; Occupations - Pastoral industry workers; Queensland Gulf country (Qld SE54)